Sm-Nd System of Rare-Metal Pegmatites of the World-Class Kolmozero Lithium Deposit and Shongui Beryllium Deposit, NW Russia: Geochemical Causes of Disturbance and Nd Mobility - Serov Pavel; Morozova Lyudmila (Russian Journal of Earth Sciences, 2025)
The Sm-Nd geochronological study was performed to investigate rare-metal pegmatites from the two unique deposits, i.e., the Kolmozero lithium deposit and Shongui deposit with beryllium mineralization (Kola Peninsula, Russia). For Kolmozero lithium deposit was obtained the Sm-Nd isochrone, corresponding to an age of 1705 ± 60 Ma with high εNd(T ) = +9.1. For Shongui beryllium deposit was obtained the Sm-Nd age, corresponding to an age of 1747 ± 33 Ma with high εNd(T ) = +9.7. This age values are close to the ages of metamorphism obtained earlier by Rb-Sr, K-Ca, and K-Ar methods. Pegmatites are characterized by a wide range of εNd(T ) values from +2 to +16 and 147Sm/144Nd ratios up to 0.3. Possible reasons for disturbance of the Sm-Nd isotope system of pegmatites are analyzed, including multicomponent mixing, fluid influence and metamorphic overprinting. The highly radiogenic signatures of rare metal pegmatites of the Shongui and Kolmozero deposits were found to appear by fractionation of Nd and Sm and their different redistribution with the change of the Sm/Nd ratio. High εNd(T ) values and changes in Sm/Nd ratios indicate the role of REE (rare-earth element) fractionation, while narrow εNd(T ) ranges suggest interaction with fluids during pegmatite formation. These findings emphasize the need for further research into the composition of fluids and their influence on isotope systems.